A Quick Glimpse into Communism and Anti-Nationalism in Kedah Before the World War Two - Mohd Kasri bin Saidon; Zolkefli bin Bahador; Khaliza binti Saidin (Proceedings of The ICECRS, 2017)
This paper is a brief review on social situation in Tanah Melayu (Malaysia), specifically in the state of Kedah, prior to World War Two. Generally, the situation and social understanding in Kedah was influenced by the influx of immigrants especially the Chinese who came for economic reasons. These immigrants brought with them the culture and the way of life in the Mainland China. This, in a way, affected people’s lives in Kedah. With the strong support from the Chinese, communism began to make its mark among other ethnic groups in the society. The Triads culture became strong and it lead to other anti-national activities. This, in turn, affected the economic, political, and social influence. All these aspects seemed to have become the foundation of a bigger influence after the surrender of Japan. They have also become the foundation for social equality and differences during the Emergency period from 1948-1960.